A quantitative determination of the chromium, copper, lead and zinc concentrations of the Jalaur River, Passi City. - Padrones, Abbie L
Water samples were collected from 5 sampling sites and analyzed for chromium, copper, lead , and zinc concentrations using the Atomic Absorption Spectrophotometer (AAS). Physico-chemical parameters such as pH, temperature, dissolved oxygen, salinity, acidity, alkalinity, particulate carbon, total solids, total dissolved solids, and the total suspended solids were also determined. Two batches of water samples were collected. The first batch was collected during the month of February while the second batch was collected during the month of March. The samples were subjected to the same analyses. The results from two sampling were averaged and compared to the data from the DENR., The pH of the water samples ranged from 5.46 to 6.20 The measured pH range was found out to be below the DENR standard for a Class C river which is 6.5 to 8.5. The dissolved oxygen (DO) of the water samples ranged from 4.80 to 6.50 ppm. There was a decrease in the DO from site 1 to site 5. The temperature ranged from 27 to 30 degrees centigrade. There was no apparent trend in the particular carbon. the alkalinity values of the water samples ranged from 103.52 to 139.64 CaCO3/L. The acidity values ranged from 29.30 to 40.50 mg CaCO3/L. Water hardness values ranged from 218.713 to 232.96 mgt CaCO3/L. The highest total solids, total dissolved solids and total suspended solids were found in site 5 with a value of 406.67, 215.50, and 194.17 mg solids /L, respectively. The lead concentrations of the samples were below the detection limit of the instrument which is 0.03 mg/L. The concentrations of the samples were below the detection limit of the instrument which is 0.03 mg/L. The concentrations of zinc in all sampling sites ranged from 0.0407 to 0.3186 ppm Zn. The concentration of zinc for sites 1 and 5, 0.3186 and 0.2501 ppm respectively was beyond the standard set by DENR which is 0.05 ppm. The copper concentrations which ranged from 0.4006 to 0.6033 ppm Cu. were all found to be beyond the standard set by the DENR (0.05 ppm Cu.) The chromium concentration ranged from 0.0120 to 0.0337 ppm Cr which were below the standard set by the DENR (0.05 ppm Cr).